Microbial diversity and bioremediation of distilleries effluent - Baskaran R; G, Ganapathy Selvam; PM, Mohan (Journal of Research in Biology, 2011)
The role of cyanobacteria in distilleries effluent was studied in Kanchipuram Tamilnadu, India. Totally 12 species of cyanobacteria belonging to 6 genera falling under 4 families were identified. Six different genera of bacteria and 3 different genera of fungi were isolated and identified. Among the cyanobacteria isolated, Nostoc muscorum was selected to treat the effluent. Distilleries effluent was the potential source of cyanobacteria. Nostoc muscorum was found to be the most dominated genus in this effluent (heterocyst organism). The inoculation of Nostoc muscorum resulted in removal of various chemicals as well as nutrients such as nitrogen, ammonia and phosphorus from the effluent. It is concluded that Nostoc muscorum, a cyanobacteria found in the distilleries effluent, could be potentially employed for the treatment of distilleries effluent